2017
DOI: 10.1016/j.enbuild.2017.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Simple thermal evaluation of building envelopes containing phase change materials using a modified admittance method

Abstract: This paper extends the admittance method to predict the diurnal energy flux reduction E r associated with adding microencapsulated phase change materials (PCM) to single and multilayer building envelopes. The effects of phase change on the thermal load through composite building walls were accounted for by modifying the decrement factor f AM and time lag ϕ AM . The procedure was demonstrated for single and multilayer PCM-composite walls subjected to a constant indoor temperature and to (i) a sinusoidal sol-air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Figures. [13][14][15][16] showed the variation of percentage of cooling load reduction as a result of using PCM for different studied cases compared with cooling load for standard room. It is important to mention that the tests for different cases of PCM were carried out at different times due to preparation requirements.…”
Section: Cooling Loads (C L): (Jun and July-2019)mentioning
confidence: 99%
See 1 more Smart Citation
“…Figures. [13][14][15][16] showed the variation of percentage of cooling load reduction as a result of using PCM for different studied cases compared with cooling load for standard room. It is important to mention that the tests for different cases of PCM were carried out at different times due to preparation requirements.…”
Section: Cooling Loads (C L): (Jun and July-2019)mentioning
confidence: 99%
“…The effect of thermal control of construction fabrics integrated with PCM in periods of extreme heat waves was previously numerically examined and the result showed that the risks of internal thermal stress can be effectively reduced without the air conditioner function [13]. A researched numerical model based on a modified acceptance model to assess the thermal performance of building conditions that are integrated with PCM and whose result converts to good compatibility with current finite element simulation results [14]. A new double walled PCM board structure was introduced, and a related simplified dynamic model was proposed, and then used to analyze the energy performance of the commercial building under various conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The result shows that the indoor heat stress risks can be reduced effectively without the function of an air conditioner. Meanwhile, Thiele et al [17] constructed a numerical model based on a modified admittance model to evaluate the thermal performance of building envelops integrated with PCM whose result turns to agree well with that of the existing finite element simulations. Zhu et al [18,19] put forward a new structure of wallboards with double shape-stabilized PCM, proposed a related simplified dynamic model, and then used it to analyze energy performance of office building under different conditions.…”
Section: Introductionmentioning
confidence: 55%
“…This is achieved by considering previous heat gains with the use of radiant time factors [15]. The CIBSE admittance method is similar, as the first calculation establishes the sensible steady-state heat gains, followed by a cyclic variation that takes into consideration the building fabric properties; an hourly thermal model can then be created due to the incorporation of coefficient and response factors [16]. However, as mentioned earlier, the ASHRAE RTS method combines radiation and convection heat transfer, which does not accommodate for conduction from the internal environment, which thereby results in overpredictions [13].…”
Section: Cibse and Ashrae Cooling Load Calculation Methodsmentioning
confidence: 99%